Diagnostic Evaluation of the School-Community Relationship: a Case of a School in Santo Domingo del Roble de Santa Bárbara de Heredia, Costa Rica - Ramírez-González, Andrea (Revista Electrónica Educare, 2015)
This paper presents the results of a participative diagnostic evaluation from a qualitative approach regarding the relationship between a primary school in Santo Domingo del Roble de Santa Bárbara de Heredia, Costa Rica and the community. The study included the participation of four teachers from upper and lower levels, as well as five parents, who are also part of two school committees, Patronato Escolar, in charge of overseeing school funds and Junta Educativa, in charge of overseeing educational matters. Some structural aspects that were considered included the curricular guidelines established by the Ministry of Public Education in regards to this topic, as well as practical teaching procedural aspects related to the communication between the school, the family and the community and school participation in rural community development projects, as an educational institution that offers and participates in formal and informal education activities and promotes community gathering by providing the facilities and resources for their improvement. Information was obtained through qualitative techniques, such as in-depth interviews and discussion groups. Data was analyzed based on three categories: professional formation, institutional outreach, and educational practice. It was concluded that the school lacks a community diagnostic or an institutional educational project that would allow for the development of concrete actions to address school and community needs. In addition, the school, represented by its teachers as leading figures, is required to participate in the organization and development of school and community projects. Teachers’ participation in the rural community is characterized by qualities, attitudes and values such as teaching vocation, leadership, organization, commitment, transparency, trust, humanism, and identification with the rural community.